PENGARUH KONSENTRASI RAGI TERHADAP MUTU HEDONIK PRODUK KERIPIK TAPE UBI JALAR UNGU (Ipomoea batatas var. ayamurasaki) - Rahmadini, Fathia; Kurnia, Pramuja Putra; Harahap, Edy Syahputra; Hidayati, Fitni; Putri, Kalasta Ayunda (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Purple sweet potato (Ipomea batatas L.) is one type of food crop with high productivity and the main agricultural product in the Karo, Simalungun, Dairi and Toba regions. The utilization of purple sweet potato as a processed food commodity has not been maximized so that innovation in processing various agricultural products is needed. One of the processed food products from purple sweet potato raw materials is tape. The purpose of this study was to develop innovations in tape products into purple sweet potato tape chips that are liked by consumers. The organoleptic panelist activities of the product were carried out by students and also the community. This study used a Factorial Completely Randomized Design with one factor studied, namely: yeast concentration factor (K) consisting of 4 treatment levels K1 = 0.5% yeast, K2 = 1% yeast, K3 = 1.5% yeast, K4 = 2% yeast. The parameters observed in this study were focused on the panelists' acceptance in terms of hedonic organoleptics, namely taste hedonic, color hedonic, aroma hedonic, and texture hedonic. The results showed that the panelists generally gave very good scores and both factors influenced the hedonic organoleptic values ??of taste, color hedonic, aroma hedonic and texture hedonic.